Pelatihan Sistem Informasi Penginputan Nilai dan Absensi Siswa Berbasis Web - Muhamad Fahmi Nugraha; Yudha Purnama (Ma'soem University, 2026)
This community service activity was motivated by the inefficiencies and recording errors caused by manual grading and attendance management at SMAN 2 Garut. This activity aims to implement and provide training on a custom-designed web-based information system for student grades and attendance as an integrated digital solution. The partners involved include teachers, administrative staff, and students. The method employed is Service Learning, encompassing preparation, hands-on training, and evaluation stages. The results indicate a significant increase in participants' digital competence, with system flow understanding reaching 95%. Participants successfully operated various functional modules, such as systematic grade inputting for teachers and face-detection-based attendance for students. The system implementation has proven to enhance data recapitulation efficiency, ensure accuracy, and facilitate real-time access to academic information. In conclusion, this training provides a tangible contribution to accelerating digital transformation, fostering a more modern, transparent, and professional school management system.